EDUCATION FINANCING MANAGEMENT IN IMPROVING THE QUALITY OF LEARNING IN SMA MUHAMMADIYAH 4 BANDUNG CITY - R. Abdurrakhim Abubakar; Fajri Abdul Sholeh; Yuyun Nurfarida; Sali Syawaliah; Nurul Hidayati Murtafiah (IAI An Nur Lampung, 2022)
process so that students actively develop their potential to have spiritual strength, self-control, personality, intelligence, noble character, and the skills they need regarding the nation and state. The purpose of national education is to develop the potential of students to become human beings who believe in and fear God Almighty, have a noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. The National Education Standards (SNP) consist of content standards, processes, educators and education personnel, graduate competencies, facilities and infrastructure, financing, management, and assessment. With the existence of these national standards, the direction of improving the quality of Indonesian education becomes more explicit, which states that the SNP's fulfillment is carried out to realize the implementation of quality education. Take part in contributing to financing education for the expected educational goals. The description presented is the use of education financing with rudimentary supervisory management techniques, and the obstacles faced by school principals in managing education financing are problems.